De alunos de projetos sociais a licenciandos em Dança na EBA/UFMG: experiências formadoras e acesso ao ensino superior - Ana Clara Lima Buratto Silva (2019)
This thesis aims to analyze how licentiate students in Dance at EBA / UFMG comprehend the possible formative experiences (Josso, 2004) lived in social projects and establish relationships between these experiences and the graduation choice for Dance. This thesis also intended to establish dialogues between the public policies of expansion and democratization of higher education in the country experienced at the beginning of the 21st century, the context of implementation of the Undergraduate Dance Course - EBA / UFMG and its student profile, considering that the research was built based on the assumption that part of the undergraduates had some background in dance in social projects before entering UFMG. We highlight that the EBA / UFMG joined strongly the Support Program for Restructuring and Expansion Plans - REUNI and its key characteristics related to the democratization of access were identified in the course of many forms, both for its night-shift operation, either by broad definition of the characteristics of the incoming student (looking for candidates who have basic knowledge in performing dance movements). The qualitative methodology was composed by the following procedures: a) documentary analysis of the relevant legislation and the Pedagogical Project of the Course (2009); b) bibliographic review of the topics addressed; c) interview with the Course Collegiate Coordinator; d) application of a questionnaire to the students of the Course ; e) interviews with undergaduates who had experiences in social projects. The survey was attended by 75% of students enrolled in the second semester of 2017. The student profile disclosed that most of the students of the Course have a quotaholder profile, regardless of whether they used the reservation space to entry into UFMG. 55% of participants reported having attended dance classes on social projects. With the interviews it was possible to meet some of the trajectories and many forms that they attach importance to social projects and attended the formative experiences witnessed. These analyzes show the significant role that social projects have played in their lives, as, among other things, they consider that the projects have contributed to their passing the UFMG Vestibular Specific Skills Tests. The research reinforces the importance of social projects in the democratization process of entry into the Course, without disregarding that teaching role of dance must be effective in Basic Education in order to be available as right of all people.